Making gender visible in family business: past and present - Pérez, Paloma Fernández; Hamilton, Eleanor (História Econômica & História de Empresas, 2012)
This study contributes to developing our understanding of gender and family business. It draws on studies from the business history and management literatures and provides an interdisciplinary synthesis. It illuminates the role of women and their participation in the entrepreneurial practices of the family and the business. Leadership is introduced as a concept to examine the roles of women and men in family ﬁrms, arguing that concepts used by historians or economists like ownership and management have served to make women ‘invisible’, at least in western developed economies in which owners and managers have been historically due to legal rules of the game men, and minoritarily women. Finally, it explores gender relations and the notion that leadership in family business may take complex forms crafte within constantly changing relationships.